Study protocol for a pragmatic randomised controlled trial in Belgian primary care and hospital settings on the effectiveness of an eHealth self-management support programme consisting of pain education and coaching of activity needs in breast cancer survivors with persistent pain: the PECAN trial - Josefien van Olmen; An De Groef; Nele Devoogdt; Lore Dams; Bart Morlion; Mira Meeus; G Lorimer Moseley; Louise K Wiles; Peter Hibbert; Patrick Neven; Ines Nevelsteen; Steffen Fieuws; et al. (BMJ Open)
Introduction Persistent pain after finishing breast cancer treatment is a common and disabling problem. The current state-of-the-art pain management advocates, in addition to biomedical (non-)pharmacological approaches, a biopsychosocial rehabilitation approach to address persistent pain, combining pain science education with promoting an active lifestyle through self-regulation techniques. We propose testing an innovative eHealth self-management support programme for this purpose in the breast cancer population with persistent pain after finishing cancer treatment. This delivery mode is believed to reduce barriers to pain self-management by providing timely, safe and cost-effective assistance addressing the biopsychosocial needs of patients. Utilising a chatbot format, the eHealth programme delivers pain science education and promotes physical activity (PA), personalised through decision-tree-based algorithms to support pain self-management. The programme aims to empower patients with understanding, coping skills and self-management techniques to reduce pain-related disability and enhance participation in daily life. The primary objective is to determine programme effectiveness compared with (1) usual care (superiority) and (2) a similar face-to-face pain self-management support programme (non-inferiority).Methods and analysis A pragmatic, three-arm randomised controlled trial was started in April 2024 at the University Hospitals of Antwerp and Leuven and primary care settings in Belgium. Participants are breast cancer survivors with persistent pain after finishing cancer treatment. Two hundred seventy participants will be randomised to one of three trial arms: (1) eHealth self-management support programme, (2) usual care or (3) a face-to-face self-management support programme. The ‘eHealth self-management support programme’ begins with a pain science education (PSE) module to initially convey key pain-related concepts and provide personalised pain management tips. Then, the programme progresses to daily activity planning to promote an active lifestyle. Guided by the Health Action Process Approach (HAPA) model, participants set and review daily activity goals and track progress. The eHealth self-management programme uses a chatbot and is accessible on any digital device. The ‘usual care programme’ involves sending the participants a study-specific brochure by postal mail and does not include any formal PSE and/or PA programmes. They may pursue or continue self-initiated care. In Belgium, usual care primarily involves pharmacological treatment, general advice on PA and the provision of informational brochures. The ‘face-to-face self-management support programme’ mirrors the eHealth intervention, combining PSE with PA coaching. It starts with three individual sessions with a trained physical therapist for biopsychosocial assessment and PSE, followed by six sessions on goal setting and active lifestyle coaching. The educational content is delivered both verbally and in written form. The primary outcome will be pain-related disability 6 months after baseline assessment. As a key secondary outcome, the effect on pain beliefs and attitudes will be investigated after the educational part of the eHealth and face-to-face programme (ie, at 6 weeks after baseline). Other secondary outcomes related to other dimensions of pain and physical-, psychosocial- and health-economic outcomes will be assessed at 12 weeks and 6 and 12 months after baseline as well.Ethics and dissemination The study will be conducted in accordance with the Declaration of Helsinki (2024). The protocol has been approved by the ethical committee of the University Hospitals of Leuven and Antwerp. Results will be disseminated via peer-reviewed scientific journals and presentations at congresses. Ethical Committee of the University Hospitals Leuven and Antwerp: BUN B3002023000132.Trial registration number ClinicalTrials.gov Identifier: NCT06308029.